Speak Up - A National Advance Care Planning Campaign in Canada. Issue 1 (1st June 2011) - Baxter, S; Chow, K; Hanvey, L
Abstract : The Canadian Hospice Palliative Care Association has established a Canadian National Advance Care Planning (ACP) Day/Campaign – Speak Up: Start the Conversation about End-of-Life Care. This campaign, which includes a national day to recognize ACP, provides an annual opportunity for individuals to discuss their wishes with family, friends and health care professionals while raising overall awareness of the importance of ACP throughout the year. The ACP day/campaign engages professionals and the public alike through partnerships, organizational events and media events. The premier day was launched on 12 April, 2011. The campaign has been launched in partnership with 16 partners, including professional associations (medicine, nursing and law); research organizations and academics; regional health authorities; health-focused non-governmental organizations; and communications experts. It was based on 2 years of work including the development of ACP in Canada: A National Framework through broad consultation with over 100 stakeholders across the country. This workshop will highlight the accomplishments of Speak Up. It will demonstrate the ways that organizations and individuals across a country are able to promote ACP in their communities. The workshop will demonstrate and describe the various resources and tools used in the campaign, and discuss the communications strategies for promoting ACP awareness. Workshop presenters will showcase toolkits for professionals and the public, a dynamic website; and poster and other promotional templates, as well as communication strategies and background resources. Participants will explore how they, their organizations and their communities could develop and become engaged in similar campaigns.